Somatotype of Taekwondo Athletes at the Regional Training Center in Valparaíso, Chile [Somatotipo de Atletas de Taekwondo del Centro de Entrenamiento Regional de Valparaíso, Chile] - Herrera-Valenzuela, T (Universidad de la Frontera, 2018)
The aim of the study was to determine the somatotype of taekwondo athletes at the Regional Training Center (CER) in Valparaíso, Chile. The first four were classified according to sex (8 athletes in total), men (18.75 ± 2.62 years) and women (18.50 ± 1.91 years), all of them active competitors in the discipline nationally and internationally. For the evaluation, the standards established by the International Society for the Advancement of Kinanthropometry (ISAK) and the Spanish Group of Cineanthropometry (GREC) were considered. The materials used were CESCORF® basic Innovare kit, TANITA® weight/height scale. To determine the somatotype, the Heath & Carter proposal was considered. The results showed that in men a classification of the somatotype of balanced mesomorph (2.5-4.0-3.0), while in women it was classified as mesomorphic -endomorphic (3,3-3,6 - 2,3). It is concluded that in both sexes the mesomorphic component predominates, women present a higher level of endomorphy and a lower development of mesomorphy compared to men. © 2018, Universidad de la Frontera. All rights reserved.